The Impact of ESG Disclosure on Firm Value in ASEAN: The Moderating Role of Audit Quality - Kusno, Herlambang Ramadhan; Novita, Santi (E-Jurnal Akuntansi, 2026)
This study aims to examine the effect of ESG on firm value and the moderating role of audit quality in the ASEAN context. Using a sample of public listed companies from 2016 to 2024, data were analyzed using panel data regression. The results indicate that ESG disclosure has a significant positive effect on firm value, suggesting that sustainability transparency serves as a credible signal to investors. Furthermore, audit quality is found to positively moderate this relationship, acting as a signal enhancer and mitigates greenwashing concerns. This research contributes to signalling theory by demonstrating how audit effort reinforces the credibility in emerging markets.